Plant Diversity that Can be Used as Silk Fabric Ecoprint Material as a Learning Resource Contextual for High School Students - Fahreza, Muh. Resky; Yani, Ahmad; Rompegading, Andi Badli (Universitas Lampung, 2023)
This study aims to find ou what types of local plants can be used as ecoprint materials of Sutra in Tempe District, Wajo and contextuallearning resources for SMA sstudents. Narrativeistic-interpretative This research was carried out from January to April 2023 and the research locations were conducted in Tempe District, Wajo Regency and in High Schools. The data analysis technique was carried out using 3 steps, namely data reduction, data presentation, and drawing conclusions. Based on the results of observations and explorations that have been carried out at the location, there are 10 types of local plants that can be used as ecoprint materials. The shape of the leaves of the ten types of plants is different, some are pinnate, finger and others. DOI: http://dx.doi.org/10.23960/jbt.v11.i2.28208